2010
DOI: 10.1007/s13258-010-0005-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two novel γ-gliadin genes encoded by K genome of Crithopsis delileana and evolution analysis with those from Triticeae

Abstract: By acid polyacrylamide gel electrophoresis (A-PAGE) analysis, it was indicated that the electrophoresis mobility of gliadins from Crithopsis delileana (Schult) Roshev (2n=2x=14, KK) had obvious difference with those from common wheat in α, γ and ω region. Using homologous primers, two γ-gliadin genes (gli-Kr1 and gli-Kr2) were isolated from C. delileana, which had been deposited in the GenBank under accession numbers EU283818 and EU283821, respectively. Two γ -gliadin genes of C. delileana had the similar prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…intermedium ssp. trichophorum [24], and C. delieana [25]. We found that the disomic addition line 59-11 had a specific band from P. huashanica in the α-gliadin section based on gliadin analysis (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…intermedium ssp. trichophorum [24], and C. delieana [25]. We found that the disomic addition line 59-11 had a specific band from P. huashanica in the α-gliadin section based on gliadin analysis (Fig.…”
Section: Discussionmentioning
confidence: 78%
“…The γ-gliadins have been considered to be the most ancient members of the wheat glutenin (Anderson et al, 2001). The molecular cloning and sequencing of these genes are helpful for better understanding the relationships of their structures and functions, and will provide vital information on gene evolution (Guo et al, 2010). In the Triticeae, γ-gliadin genes have been cloned from the genus Triticum (Anderson et al, 2001;Qi et al, 2009;Altenbach et al, 2010), Aegilops (Qi et al, 2009;Huang et al, 2010), Thinopyrum , and Crithopsis (Guo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%